High-molecular composite material with relatively low curie point and positive temperature coefficient as well as preparation method and application of high-molecular composite material
By using fatty acids and LDPE and other materials in PTC materials, the conductive network structure is formed, and the problems of high Curie temperature and NTC effects of PTC materials are solved, and polymer composite materials with low Curie temperature and high PTC strength are realized, suitable for humans Contact electronic equipment and simplify production processes.
Patent Information
- Application Number
- CN202411363902.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-28
AI Technical Summary
The existing PTC materials have high Curie temperature, large room temperature resistivity, poor repeatability, and are prone to NTC effects, making it difficult to meet the needs of the room temperature segment.
Fatty acids are used as phase change material, combined with LDPE as support material and carbon-based conductive particles as conductive fillers, and a polymer composite with a lower Curie point positive temperature coefficient is prepared by solution method to form a conductive network structure to prevent the flow of the molten state and weaken it. NTC effect.
It achieves a low Curie temperature point and high PTC strength. The Curie temperature of the material is close to the human body temperature, has low room temperature resistivity and high PTC strength. It is suitable for human contact electronic equipment, and has a simple process and low cost.
Smart Images

Figure CN119241934A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer positive temperature coefficient thermistor materials (PPTC materials, Polymer Positive Temperature Coefficient Material), and in particular relates to a low Curie point positive temperature coefficient polymer composite material and a preparation method and application thereof. Background Art
[0002] PTC (Positive Temperature Coefficient) material is a thermistor material with a positive temperature coefficient effect. The resistivity of PTC material remains basically unchanged or changes only slightly at low temperatures; when the temperature exceeds the Curie temperature, the resistivity of PTC material increases sharply with increasing temperature. This phenomenon is called the PTC effect. The opposite of the PTC effect is the NTC (Negative Temperature Coefficient) effect, which is the effect that the resistivity of the material decreases with increasing temperature. The NTC effect should generally be avoided during the use of positive temperature coefficient materials. At normal temperature, the conductive particles form a low-resistance conductive network in the matrix. However, when the temperature rises above the operating temperature of the device, whether caused by high current flowing through the device or by increased ambient temperature, the grains in the matrix melt and form an amorphous state. During the melting of the crystalline phase, the increase in volume separates the conductive particles on the conductive chain, resulting in a nonlinear increase in the resistance of the PTC device by three or more orders of magnitude. The research and development of PTC materials are relatively extensive, but the research and application of PTC materials are mainly limited to the high-temperature field. This is mainly because the Curie temperature of widely used polymer-based PTC composite materials is generally high (50-300°C), which is difficult to meet the use requirements in the normal temperature range.
[0003] Patent CN116959825A discloses a thermistor and a self-feedback flexible microheater and its preparation method and application. The heater has a Curie temperature of 35°C, but its room temperature resistance is relatively high and its PTC strength is also relatively low. In the field of high-temperature PTC materials, patent CN118271724A discloses a high room temperature conductivity polymer-based PTC material and a preparation method. The polymer-based composite material has an extremely low room temperature resistivity and can reach a PTC strength of more than 7.38. In the field of low-temperature PTC materials, patent CN117736525A uses a hydrothermal method to prepare a porous carbon metal oxide / polyvinylidene fluoride conductive composite material, which has a low room temperature resistance and a Curie temperature of around 30°C, but its PTC strength is not high.
[0004] At present, some researchers have prepared a series of polymer-based PTC materials with room temperature Curie temperature using paraffin or EVA as matrix materials, but these materials still have the problems of high low temperature resistivity and poor PTC repeatability, and there are still some disadvantages in practical applications. Similarly, some researchers have also used the melting method to prepare low Curie temperature PTC materials. Although the materials have low Curie temperature and low room temperature resistivity, the uniformity of mixing is also a big problem. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a low Curie point positive temperature coefficient polymer composite material and its preparation method and application. The composite material uses fatty acid as a phase change material and LDPE as a supporting material to overcome the problems of existing PTC materials such as high Curie temperature, high room temperature resistivity, poor repeatability and easy occurrence of NTC effect.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A low Curie point positive temperature coefficient polymer composite material comprises the following raw materials in percentage by mass: 38.46-76.25% fatty acid, 12.82-47.65% random copolymer and 4.69-23.08% conductive filler.
[0008] Furthermore, the fatty acid is one or more of myristic acid, palmitic acid, stearic acid and normal alkane acid derivatives.
[0009] Furthermore, the random copolymer is one or more of polyvinylidene fluoride, high-density polyethylene, low-density polyethylene, linear low-density polyethylene and ultra-high molecular weight polyethylene materials.
[0010] Furthermore, the conductive filler is carbon-based conductive particles; the carbon-based conductive particles are one or both of carbon black and graphite powder.
[0011] The present invention also provides a method for preparing the relatively low Curie point positive temperature coefficient polymer composite material, comprising the following steps:
[0012] Dissolving the random copolymer in xylene and stirring evenly to obtain a dissolved material;
[0013] The dissolved material, fatty acid and conductive filler are stirred uniformly to obtain a solution mixture;
[0014] Drying the solution mixture in a vacuum oven to obtain a mixture;
[0015] The mixed material is subjected to molding treatment to obtain a polymer composite material with a lower Curie point and a positive temperature coefficient.
[0016] Furthermore, in the process of preparing the dissolved material, the stirring speed is 300-900 rpm and the heating temperature is 60-120°C; in the process of preparing the solution mixed material, the stirring speed is 300-900 rpm, the time is 0.5-5h, and the heating temperature is 60-120°C.
[0017] Furthermore, the drying temperature is 60-100°C.
[0018] The present invention also provides an application of the relatively low Curie point positive temperature coefficient polymer composite material in the preparation of a positive temperature coefficient material.
[0019] Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] The low Curie point positive temperature coefficient polymer composite material of the present application adopts a random copolymer as the supporting matrix of the composite material. Since the random copolymer has a relatively large melting point and high viscosity, the conductive filler plays the role of forming a conductive network structure. After the fatty acid melts and destroys the conductive network, the flow of the molten fatty acid can be blocked, and the conductive network can be prevented from reforming, thereby effectively weakening the NTC effect. At the same time, due to the addition of low-melting-point fatty acids, the material resistance of the low Curie point positive temperature coefficient polymer composite material can undergo a large mutation near the melting point of the fatty acid phase change material, thereby achieving a low Curie temperature point and a very high PTC strength.
[0021] The low Curie point positive temperature coefficient polymer composite material prepared by the present invention has a Curie temperature (38-43°C) close to human body temperature, and at the same time has a very low room temperature resistivity and a high PTC strength, which makes up for the shortcomings of the current PTC materials with a Curie temperature in the room temperature range, such as high room temperature resistance, low PTC strength and obvious NTC effect.
[0022] The low Curie point positive temperature coefficient polymer composite material prepared by the present invention has a Curie temperature close to human body temperature and has good application prospects in electronic devices that have more contact with the human body.
[0023] The invention adopts a solution method for preparation, has a simple process, is easy to control production conditions, uses cheap raw materials, has low production cost, and has great industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0025] Figure 1 The temperature resistance diagram of the low Curie point positive temperature coefficient polymer composite material of Example 3;
[0026] Figure 2 This is a comparison chart of the temperature resistance of the low Curie point positive temperature coefficient polymer composite material of Example 3 and Comparative Example 3;
[0027] Figure 3 This is a comparison chart of the temperature resistance of low Curie point positive temperature coefficient polymers of Example 1, Example 2, Example 4, and Comparative Example 1. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] The present invention provides a method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient. The composite material includes a polymer matrix and a conductive filler uniformly distributed in the polymer matrix. In some preferred embodiments, the polymer matrix includes a random copolymer and a fatty acid. The specific preparation method includes the following steps:
[0034] (1) dissolving the random copolymer in xylene and stirring uniformly to obtain a dissolved material;
[0035] (2) stirring the dissolved material, fatty acid and conductive filler to obtain a solution mixture;
[0036] (3) drying the solution mixture in a vacuum oven to obtain a mixture;
[0037] (4) The mixed material is subjected to molding treatment to obtain a polymer composite material with a low Curie point and a positive temperature coefficient.
[0038] In some preferred embodiments, in step (1), the stirring speed is 500-800 rpm, preferably at 500 rpm until dissolved; the stirring is performed under heating conditions, and the heating temperature is 70-110° C. When the stirring temperature is lower than 60° C., the random polymer is difficult to dissolve in xylene, and when the stirring temperature is higher than 120° C., due to the high temperature, the phase change material and the solvent will volatilize to a certain extent, which is not conducive to processing, so the temperature is preferably 80-85° C.
[0039] In some preferred embodiments, in step (2), the stirring speed is 400-900 rpm (preferably 500-800 rpm), the time is 0.5-3 h (preferably 10-60 min), and the stirring is carried out under heating conditions, and the heating temperature is 60-110° C. (preferably 80-83° C.).
[0040] In some more preferred embodiments, step (2), stirring is performed in two steps, specifically: first, mixing at a temperature of 80-85° C. and a rotation speed of 500 rpm for 5-10 min, and then adjusting the rotation speed to 800 rpm and mixing for 30-120 min to obtain a solution mixture.
[0041] In some preferred embodiments, in step (3), the drying temperature in the vacuum oven is 60-100° C., preferably 80-90° C. for 4-12 h.
[0042] The Curie temperature of the low Curie point positive temperature coefficient polymer composite material prepared by the above method is 38-43°C, and the composite material specifically comprises the following raw materials in mass percentage: 38.46-76.25% fatty acid, 12.82-47.65% random copolymer and 4.69-23.08% conductive filler. Among them, when the mass percentage of the random copolymer is less than 12.82% and the mass percentage of the fatty acid is greater than 76.25%, the synthesized positive temperature coefficient polymer material cannot maintain the shape of the material after heating due to too little random polymer and is easy to collapse; when the mass percentage of the random copolymer is greater than 47.65% and the mass percentage of the fatty acid is less than 38.46%, due to the excessive mass percentage of the random copolymer, the conductive network of the positive temperature coefficient polymer material cannot be completely destroyed when the temperature rises, resulting in a weakened PTC effect at a lower temperature. A better effect can be achieved when the mass ratio of the random copolymer to the phase change material is around 1:3.
[0043] In some preferred embodiments, the fatty acid is one or more of myristic acid, palmitic acid, stearic acid and normal alkane acid derivatives, preferably palmitic acid or stearic acid. These fatty acids play a role in making the conductive filler disperse more evenly inside, making the conductive grid more dense, and making the conductive filler have low filling and low room temperature resistance.
[0044] In some preferred embodiments, the random copolymer is polyvinylidene fluoride, high-density polyethylene (HDPE, density 0.941-0.960 g / cm 3 ), low-density polyethylene (LDPE, density 0.91-0.93g / cm 3 ), linear low-density polyethylene (LLDPE, density 0.918-0.935g / cm 3 ) and ultra-high molecular weight polyethylene (UHMWPE, density 0.920-0.964g / cm 3 ), preferably LDPE. These random copolymers play the role of supporting materials in the positive temperature coefficient polymer material, which can not only ensure that the material will not collapse when the ambient temperature reaches the melting point of the fatty "size" acid, but also provide the positive temperature coefficient polymer material with excellent electrical properties and temperature response performance.
[0045] In some preferred embodiments, the conductive filler is carbon-based conductive particles; the carbon-based conductive particles are carbon black or graphite powder. These conductive fillers play a role in forming a conductive network structure.
[0046] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0047] The raw materials used in the following examples and comparative examples of the present invention are all commercially available products known to those skilled in the art. Among them, LDPE, LLDPE, HDPE, EVA12, EVA18, conductive carbon black, and graphite powder were purchased from Shanghai Titan Technology Co., Ltd. (Adamas); xylene and stearic acid were purchased from Shanghai Titan Technology Co., Ltd. (Greagent).
[0048] The technical solution of the present invention is further illustrated by the following embodiments.
[0049] Example 1
[0050] A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient, the specific steps are as follows:
[0051] (1) Dissolve 3.6 g of LDPE in 36 mL of xylene, set the oil bath temperature to 80° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0052] (2) adding 3.6 g of palmitic acid and 2.16 g of graphite to the above dissolved material, mixing for 10 min at a temperature of 80° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 60 min to obtain a solution mixture;
[0053] (3) Pour the solution mixture into an evaporating dish, dry it in a vacuum oven at 80°C for 6 hours to evaporate the xylene, and cool it to room temperature to obtain a mixture;
[0054] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC1.
[0055] Example 2
[0056] A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient, the specific steps are as follows:
[0057] (1) Dissolve 1.2 g of LDPE in 12 mL of xylene, set the oil bath temperature to 80° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0058] (2) adding 6 g of palmitic acid and 2.16 g of graphite to the above-mentioned dissolved material, mixing for 10 min at a temperature of 80° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 30 min to obtain a solution mixture;
[0059] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 80°C for 6 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0060] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC2.
[0061] Example 3
[0062] A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient, the specific steps are as follows:
[0063] (1) Dissolve 1.2 g of LDPE in 12 mL of xylene, set the oil bath temperature to 83° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0064] (2) adding 3.6 g of palmitic acid and 1.2 g of graphite to the above dissolved material, mixing for 5 min at a temperature of 83° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 60 min to obtain a solution mixture;
[0065] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 90°C for 12 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0066] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC3.
[0067] Example 4
[0068] A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient, the specific steps are as follows:
[0069] (1) Dissolve 1 g of LDPE in 10 mL of xylene, set the oil bath temperature to 85° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0070] (2) adding 3 g of stearic acid and 1.2 g of graphite to the above-mentioned dissolved material, mixing for 10 min at a temperature of 85° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 120 min to obtain a solution mixture;
[0071] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 80°C for 6 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0072] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC4.
[0073] Example 5
[0074] A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient, the specific steps are as follows:
[0075] (1) Dissolve 1.4 g of LDPE in 14 mL of xylene, set the oil bath temperature to 85° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0076] (2) adding 4.2 g of stearic acid and 1.2 g of graphite to the above-mentioned dissolved material, mixing for 5 min at a temperature of 85° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 100 min to obtain a solution mixture;
[0077] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 88°C for 5 h to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0078] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC5.
[0079] Comparative Example 1
[0080] A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient, the specific steps are as follows:
[0081] (1) Dissolve 1.3 g of EVA12 in 13 mL of xylene, set the oil bath temperature to 83 °C, the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0082] (2) adding 5.2 g of palmitic acid and 0.32 g of carbon black to the above-mentioned dissolved material, mixing for 10 min at a temperature of 83° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 60 min to obtain a solution mixture;
[0083] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 90°C for 4 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0084] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC6.
[0085] Comparative Example 2
[0086] A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient, the specific steps are as follows:
[0087] (1) Dissolve 3.25 g of EVA12 in 32.5 mL of xylene, set the oil bath temperature to 70° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0088] (2) adding 3.25 g of palmitic acid and 0.32 g of carbon black to the above-mentioned dissolved material, mixing for 15 min at a temperature of 70° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 30 min to obtain a solution mixture;
[0089] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 70°C for 12 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0090] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC7.
[0091] Comparative Example 3
[0092] A method for preparing a common PTC composite material (without fatty acid as phase change material), the specific steps are as follows:
[0093] (1) Dissolve 4.8 g of LDPE in 48 mL of xylene, set the oil bath temperature to 80° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0094] (2) adding 1.2 g of graphite to the above-mentioned dissolved material, mixing for 10 min at a temperature of 80° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 60 min to obtain a solution mixture;
[0095] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 80°C for 6 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0096] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC8.
[0097] Comparative Example 4
[0098] A method for preparing a common PTC composite material (without fatty acid as phase change material), the specific steps are as follows:
[0099] (1) Dissolve 4.8 g of EVA12 in 48 mL of xylene, set the oil bath temperature to 80° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0100] (2) adding 1.2 g of graphite to the above-mentioned dissolved material, mixing for 10 min at a temperature of 80° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 60 min to obtain a solution mixture;
[0101] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 80°C for 6 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0102] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC9.
[0103] Comparative Example 5
[0104] A method for preparing a common PTC composite material (without fatty acid as phase change material), the specific steps are as follows:
[0105] (1) Dissolve 6.5 g of EVA12 in 48 mL of xylene, set the oil bath temperature to 80° C., the rotation speed to 500 rpm, and stir until the random copolymer is completely dissolved to obtain a dissolved material;
[0106] (2) adding 0.98 g of graphite to the above-mentioned dissolved material, mixing for 10 min at a temperature of 80° C. and a rotation speed of 500 rpm, then adjusting the rotation speed to 800 rpm and mixing for 60 min to obtain a solution mixture;
[0107] (3) Pour the solution mixture into an evaporating dish and dry it in a vacuum oven at 80°C for 6 hours to evaporate the xylene, then cool it to room temperature to obtain a mixture;
[0108] (4) The mixture was pressed into a disc sample with a diameter of 10 mm and a thickness of 0.75 mm by a hot press, and cooled to room temperature to obtain a low Curie point PTC composite material, which was recorded as PTC10.
[0109] Comparative Example 6
[0110] The same as Example 3, except that the amount of LDPE added is 0.3 g, the amount of palmitic acid added is 3.7 g, and the amount of graphite added is 1.2 g. A low Curie point PTC composite material is obtained, which is recorded as PTC11.
[0111] Comparative Example 7
[0112] Same as Example 3, except that the mass of palmitic acid is replaced by tetradecanol to obtain a low Curie point PTC composite material, which is recorded as PTC12.
[0113] The composition conditions of the low Curie point PTC composite materials PTC1-12 prepared above are summarized, and the low temperature resistivity (ρ15°C), Curie temperature and PTC strength (P=Lg(ρ max / ρ min , ρ max is the maximum resistivity of the material, ρ min The minimum resistivity of the material was tested, and the test results of various performances are shown in Table 1.
[0114] Table 1 is a comparison table of raw material composition, low temperature resistivity, Curie temperature and PTC strength of Examples 1-5 and Comparative Examples 1-7
[0115]
[0116] As can be seen from Table 1, when the mass ratio of fatty acids to LDPE is 1:3, the composite material can have both low room temperature resistivity and high PTC strength. As the mass percentage of random copolymer increases, due to the excessive mass percentage of random copolymer, the conductive network of the positive temperature coefficient polymer material cannot be completely destroyed when the temperature rises, resulting in the weakening of the PTC effect at lower temperatures and the failure to achieve the purpose of a low Curie temperature composite material. At the same time, due to the increase in the mass fraction of random copolymers, it is more difficult to form a conductive path in the composite material, resulting in a higher room temperature resistivity of the material. When too little random copolymer is added, the shape of the material cannot be maintained after heating, and it is easy to collapse and cannot reach a higher resistance value, resulting in a low PTC strength.
[0117] Figure 1 This is the temperature resistance diagram of the low Curie point positive temperature coefficient polymer composite material of Example 3; it can be seen from the figure that the material can have a large resistance increase behavior at 60°C and can have good stability before 80°C.
[0118] Figure 2 This is a temperature resistance comparison diagram of the low Curie point positive temperature coefficient polymer composite material of Example 3 and Comparative Example 3; it can be seen from the figure that the composite material without the addition of phase change material not only has a higher room temperature resistance, but also has a lower PTC strength than the composite material with the addition of phase change material.
[0119] Figure 3The figure is a comparison chart of the temperature resistance of the low Curie point positive temperature coefficient polymer of Example 1, Example 2, Example 4 and Comparative Example 1. It can be seen from the figure that the composite material with EVA as the copolymer has a higher room temperature resistance and a slower heating rate than the composite material with LDPE as the copolymer.
[0120] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A polymer composite material with a low Curie point and a positive temperature coefficient, characterized in that: The invention comprises the following raw materials in percentage by mass: 38.46-76.25% of fatty acid, 12.82-47.65% of random copolymer and 4.69-23.08% of conductive filler.
2. The low Curie point positive temperature coefficient polymer composite material according to claim 1, characterized in that: The fatty acid is one or more of myristic acid, palmitic acid, stearic acid and normal alkane acid derivatives.
3. The low Curie point positive temperature coefficient polymer composite material according to claim 1, characterized in that: The random copolymer is one or more of polyvinylidene fluoride, high-density polyethylene, low-density polyethylene, linear low-density polyethylene and ultra-high molecular weight polyethylene materials.
4. The low Curie point positive temperature coefficient polymer composite material according to claim 1, characterized in that: The conductive filler is carbon-based conductive particles; the carbon-based conductive particles are one or both of carbon black and graphite powder.
5. A method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Dissolving the random copolymer in xylene and stirring evenly to obtain a dissolved material; The dissolved material, fatty acid and conductive filler are stirred uniformly to obtain a solution mixture; Drying the solution mixture in a vacuum oven to obtain a mixture; The mixed material is subjected to molding treatment to obtain a polymer composite material with a lower Curie point and a positive temperature coefficient.
6. The method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient according to claim 5, characterized in that: In the process of preparing the dissolved material, the stirring speed is 300-900 rpm and the heating temperature is 60-120° C.; in the process of preparing the solution mixed material, the stirring speed is 300-900 rpm, the time is 0.5-5h, and the heating temperature is 60-120° C.
7. The method for preparing a polymer composite material with a low Curie point and a positive temperature coefficient according to claim 5, characterized in that: The drying temperature is 60-100°C.
8. Use of the low Curie point positive temperature coefficient polymer composite material according to any one of claims 1 to 4 in the preparation of positive temperature coefficient materials.
Citation Information
Patent Citations
Low-resistivity positive temperature coefficient type conductive polymer composite material and preparation method thereof
CN101633787A
Method for preparing composite conductive polyethylene carbon black material with improved positive temperature coefficient performance
CN102093617A
Preparation method and application for fatty acid / polymer shaped phase-change superfine complex fiber
CN102605463A
Low-Curie-temperature-point positive temperature coefficient (PTC) organic composite material and preparation method thereof
CN108503940A
Planar heating element, water-based conductive paste for planar heating element and preparation method of water-based conductive paste
CN115304989A
